BTEX compositions and its potential health impacts in Malaysia. (December 2019) - Latif, Mohd Talib; Abd Hamid, Haris Hafizal; Ahamad, Fatimah; Khan, Md Firoz; Mohd Nadzir, Mohd Shahrul; Othman, Murnira; Sahani, Mazrura; Abdul Wahab, Muhammad Ikram; Mohamad, Noorlin; Uning, Royston; Poh, Seng Chee; Fadzil, Muhammad Fais; et al.
Abstract: This study aims to determine the composition of BTEX (benzene, toluene, ethylbenzene and xylene) and assess the risk to health at different sites in Malaysia. Continuous monitoring of BTEX in Kuala Lumpur City Centre, Kuala Terengganu, Kota Kinabalu and Fraser Hill were conducted using Online Gas Chromatograph. For comparison, BTEX at selected hotspot locations were determined by active sampling method using sorbent tubes and Thermal Desorption Gas Chromatography Mass Spectrometry. The hazard quotient (HQ) for non-carcinogenic and the life-time cancer risk (LTCR) of BTEX were calculated using the United States Environmental Protection Agency (USEPA) health risk assessment (HRA) methods. The results showed that the highest total BTEX concentrations using continuous monitoring were recorded in the Kuala Lumpur City Centre (49.56 ± 23.71 μg/m 3 ). Toluene was the most dominant among the BTEX compounds. The average concentrations of benzene ranged from 0.69 ± 0.45 μg/m 3 to 6.20 ± 3.51 μg/m 3 . Measurements using active sampling showed that BTEX concentrations dominated at the roadside (193.11 ± 114.57 μg/m 3 ) in comparison to petrol station (73.08 ± 30.41 μg/m 3 ), petrochemical industry (32.10 ± 13.13 μg/m 3 ) and airport (25.30 ± 6.17 μg/m 3 ). Strong correlations among BTEX compounds ( p <0.01, r >0.7) at Kuala Lumpur City Centre showed that BTEX compounds originated from similar sources. The values of HQ at all stations were <1 indicating the non-carcinogenic risk are negligible and do not pose threats to human health. The LTCR value based on benzene inhalation (1.59 × 10 −5 ) at Kuala Lumpur City Centre were between 1 × 10 −4 and 1 × 10 −5, representing a probable carcinogenic risk. Highlights: BTEX were determined using continuous and active sampling. Toluene was the most dominant among the BTEX compounds. Motor vehicles are main source of BTEX at urban sites. HQ values suggest non-carcinogenic risk is negligible. LTCR based on benzene inhalation in urban sites show probable carcinogenic risk.